A bitter pill to swallow? Patterns of critical consciousness and socioemotional and academic well-being in early adolescence - Godfrey, Erin B; Burson, Esther L; Yanisch, Tess M; Hughes, Diane; Way, Niobe (Developmental psychology, 2019)
An increasing body of research on critical consciousness explores how youth understand and react to inequality in their social contexts. The operationalization of critical consciousness remains inchoate, however. Developmental psychology traditionally conceptualizes critical consciousness as three components (critical reflection, political efficacy, and critical action), but how levels of these components combine for different youth or relate to outcomes remains unclear. This article uses latent class analysis to examine how components of critical consciousness pattern together in a sample 448 of marginalized (racial/ethnic minority) youth, and relate to demographic characteristics, socioemotional outcomes, and academic well-being. We identify four classes of critical consciousness components differentiated by their level of critical reflection, beliefs about the fairness of the United States, and external and internal political efficacy. Ethnicity was related to class membership, but gender and socioeconomic status were not. Controlling for race/ethnicity, we find differences in cross-sectional measures of depression, academic engagement, academic competence, and grades of youth across these classes and identify sociopolitical efficacy as a key predictor of positive youth development. Our findings provide theoretical clarity and practical insight into the complexity of critical consciousness and the combination of components that is most beneficial for positive youth development. (PsycINFO Database Record (c) 2019 APA, all rights reserved).